Diaspora, Maladjustment, and Hybridity in American and Pakistani Novels: A Comparative Study of Nafisa Haji and Bina Shah - Nadia, Bibi; Doering, Ole (Educalitra: English Education, Linguistics, and Literature Journal, 2024)
The Pakistani diaspora in the United States confronts a range of challenges arising from the interplay of ethnicity, nationality, and religious identity. Central to these challenges is the task of reconciling deeply held religious beliefs with the prevailing norms and practices of American society. This study investigates the complexities of integrating religious faith into a culturally hybrid identity through the lens of Homi Bhabha’s theory of cultural hybridity. By analysing the novels Writing on the Forehead by Nafisa Haji and Where to Dream in a Blue Moon by Bina Shah, this research explores the dynamics of cultural convergence and its implications for diasporic communities. These works offer insights into how Pakistani immigrants navigate the tension between maintaining religious fidelity and adapting to new cultural contexts. The study reveals that while the process of hybridization presents significant challenges, it also offers opportunities for enriching religious experiences and fostering intercultural dialogue. The findings underscore the importance of understanding the nuanced interplay between traditional religious practices and the evolving cultural landscape of the diaspora. This research contributes to broader discussions on multiculturalism, religious pluralism, and social cohesion, highlighting the role of literature in depicting and addressing these complex issues. Future studies should further explore how hybrid identities develop over time and the impact of generational shifts within diasporic communities on religious and cultural integration.